(untitled) (Italian Journal of Public Health, 2007)
Background: During the last two decades, tuberculosis (TB) has once again emerged as a significant public health problem in Western Countries. The aim of this study is to describe the epidemiology of TB in Italy in the last fifteen years. All routine information sources available (annual notifications, mortality and hospital discharges) were used, and attempts to investigate gender and geographical differences were made. Methods: Age-standardized annual notification, mortality and hospital discharge rates were calculated. Time trends of annual notifications, mortality and hospital discharges for TB were modelled through Poisson regression, and whenever necessary, negative binomial regression. Results: The analysis of the temporal trend of TB using the three indicators shows an increase until the middle of 1990s and a following decrease. TB is more frequent in men than in women, with a decremental. North to South gradient. There are important geographical and gender differences of the TB decline in Italy, since the decrease of TB frequency is more pronounced in men than in women and it is less evident in the central and, to a lesser extent, the southern parts of the country. Discussion: Italian guidelines for TB control, which are largely consistent with the international recommendations for low-incidence countries, need to be fully implemented throughout the entire country in order to reach the ultimate goal of disease eradication. Given the high number of TB cases among foreignborn persons, a strong public health commitment on TB control for immigrants, which includes screening, prophylaxis and treatment, is urgently needed.